Why a gender approach is important for conservation: a case study in Sarawak, Malaysia - Castello, A. del (Bioversity International and the International Center for Tropical Agriculture, 2016)
Every year on October 15th, the UN celebrates International Day of Rural Women to honor and recognize the importance of rural women in enhancing agricultural rural development worldwide. The following story highlights the importance of integrating female and male knowledge in the conservation and management of native fruit trees in Malaysia.